2018
DOI: 10.1093/nar/gky056
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of a mammalian splicing enhancer

Abstract: Exonic splicing enhancer (ESE) sequences are bound by serine & arginine-rich (SR) proteins, which in turn enhance the recruitment of splicing factors. It was inferred from measurements of splicing around twenty years ago that Drosophila doublesex ESEs are bound stably by SR proteins, and that the bound proteins interact directly but with low probability with their targets. However, it has not been possible with conventional methods to demonstrate whether mammalian ESEs behave likewise. Using single molecule mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 76 publications
3
52
0
Order By: Relevance
“…However, it is in agreement with recent observations indicating that the interaction of a splicing factor with a binding motif depends on the sequence context and on the presence of clusters of related binding motifs (Zhang et al 2013;Cereda et al 2014;Fu and Ares 2014;Dominguez et al 2018;Jobbins et al 2018). For example, increasing the exonic frequency of GGAlike motifs increases the probability of an exon to be regulated by the SRSF1 splicing factor that binds to GGAGGA-like motifs although only one binding site is used (Jobbins et al 2018). In this setting, we observed similar nucleotide and amino acid composition biases when analyzing exons regulated by a splicing factor or exons containing CLIP-related signals for the same splicing factor (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, it is in agreement with recent observations indicating that the interaction of a splicing factor with a binding motif depends on the sequence context and on the presence of clusters of related binding motifs (Zhang et al 2013;Cereda et al 2014;Fu and Ares 2014;Dominguez et al 2018;Jobbins et al 2018). For example, increasing the exonic frequency of GGAlike motifs increases the probability of an exon to be regulated by the SRSF1 splicing factor that binds to GGAGGA-like motifs although only one binding site is used (Jobbins et al 2018). In this setting, we observed similar nucleotide and amino acid composition biases when analyzing exons regulated by a splicing factor or exons containing CLIP-related signals for the same splicing factor (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, splicing factor binding sites are unlikely to be defined by their sole nucleotide composition bias. For example, it has been recently shown that RNA binding sites are within specific context and that some RNA binding sites correspond to spaced "bipartite" short linear motifs (Zhang et al 2013;Cereda et al 2014;Fu and Ares 2014;Dominguez et al 2018;Jobbins et al 2018). By dissecting each RNA binding site, their flanking nucleotide preferences, their clustering, and the space between them, it would be possible to better characterize the way they can affect codon and amino acid usage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with that notion, individual mutations did not markedly vary in the splicing response to the SRSF1 knockdown. This may have been related to requirement of multiple SRSF1 binding sites to ensure the knockdown's function, as described by Jobbins et al [60]. Therefore, a single nucleotide substitution might not have significantly harmed the SRSF1 binding.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is in agreement with recent observations indicating that the interaction of a splicing factor with a binding motif depends on the sequence context and on the presence of clusters of related binding motifs 3–7 . For example, increasing the exonic frequency of GGA-like motifs increases the probability of an exon to be regulated by the SRSF1 splicing factor that binds to GGAGGA-like motifs even though only one binding site is used 6 .…”
Section: Discussionmentioning
confidence: 99%